Impact of using the imaginative learning strategy on the comprehension level of historical events among the fourth grade students in Southern Badia Directorate - El-Jazi, Rania Abdel Kareme (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the impact of using the imaginative learning strategy on the comprehension level of historical events among the fourth grade students. To achieve the objectives of the study, the semi-experimental approach was adopted due to its suitability to the nature and objectives of the research. The researcher prepared instructional plans for the lessons of the sixth unit of the fourth grade book through the use of the imaginative learning strategy. She also prepared a test for the comprehension of the historical events and applied it to a sample of (73) female students from Rashid Elementary Mixed School of the Southern Badia Directorate in Ma’an province, which was intentionally selected. The sample members were distributed to two groups: experimental who studied the book by using the imaginative learning strategy and the control group who used the traditional method. After conducting the statistical analysis, it was found that there was an impact on the use of the imaginative learning strategy on the comprehension level of historical events among the fourth grade students
Keywords: imaginative learning strategy; comprehension of historical events; fourth grade students